A Desain Sarana Bawa Bagi Pelaku UMKM Salad Buah di Bazaar - Nadia Zulfa; Maharani Dian Permanasari (Jurnal Desain Produk Nasional, 2024)
This research aims to design a functional carrying solution for micro, small, and medium enterprises (MSMEs) that sell fruit salad at bazaars. An optimal carrying design can help improve operational efficiency and comfort for business operators in transporting their products. The research methodology uses the design thinking method due to its user-centered approach, ensuring the resulting solutions are tailored to their needs and preferences. The research process consists of five main stages: empathy, definition, ideation, prototyping, and testing. In the empathy stage, the research is conducted by analyzing user needs through interviews and observations to gain a deep understanding of the challenges faced by MSMEs during bazaars. The next stage involves further exploration of design and configuration, as well as the selection of appropriate materials. The results of this study show that the designed carrying solution features compartments that accommodate the sizes of tools and complementary materials brought to bazaars, and is made from durable, easy-to-clean materials. The implementation of the design thinking method in designing the carrying solution for MSME fruit salad vendors at bazaars is expected to produce a functional solution, improve operational efficiency, and meet the needs of fruit salad MSMEs. This solution will make a significant contribution to supporting the growth of MSMEs in the culinary sector.